Optimalisasi Aksesibilitas Pemegang Paten melalui Implementasi Sistem Peringatan Dini dan Penghidupan Kembali (SIPARKA) guna Mengakselerasi Pertumbuhan Ekonomi Nasional - Sakana, Ratnamaya Aqila Putri; Nashrullah, Ahmad Isa; Pebriani, Yesi (Forschungsforum Law Journal, 2025)
Patent protection plays a significant role in enhancing public contributions toward the creation of innovations that drive national economic growth. In line with this objective, the Government of Indonesia has accommodated efforts to protect patents through Law Number 13 of 2016 concerning Patents, along with its subsequent amendments. However, the existing regulatory framework still presents several issues, particularly in terms of preventing patent lapses due to delayed payment of annual fees and the suboptimal process of patent reinstatement through the Commercial Court. This study employs a doctrinal legal research method by analyzing secondary sources, including legal regulations and relevant literature, to examine the core issues. Based on the findings, the author proposes the development of a mechanism known as Sistem Peringatan Dini dan Penghidupan Kembali Paten (SIPARKA), aimed at addressing the inadequacies in both the prevention of patent lapses and the reinstatement process. In its implementation, SIPARKA will be optimized through the introduction of a Three Patent Warnings feature and a reinstatement procedure facilitated by the Patent Appeal Commission. Through this mechanism, it is expected that the issues related to the prevention and reinstatement of lapsed patents can be effectively addressed, thereby ensuring legal certainty.